Reticulate Skin Lesions: Practical Color-Based Algorithm for Initial Clinical Assessment; [Lesiones Cutáneas Reticulares: Algoritmo Clínico Práctico Basado en el Color de la Lesión Para el Abordaje Inicial] - Fuenzalida-Cruz, H; Loubies-Muñoz, R; Pincheira-Figueroa, L; Aedo-Inostroza, G (Elsevier Doyma, 2023)
Reticular patterns are observed in a great variety of skin diseases. While these morphologic patterns are often highly distinctive, they are seldom discussed or studied in clinical contexts or recognized as a diagnostic category in their own right. Diseases presenting with reticulate skin lesions have multiple etiologies (tumors, infections, vascular disorders, inflammatory conditions, and metabolic or genetic alterations) and can range from relatively benign conditions to life-threatening ones. We review a selection of these diseases and propose a clinical diagnostic algorithm based on predominant coloring and clinical features to aid in their initial assessment. © 2023 AEDV